2009
DOI: 10.1111/j.1399-3046.2008.00918.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Ig‐null B lymphocytes in the peripheral blood of pediatric solid organ transplant recipients with elevated Epstein‐Barr viral loads

Abstract: In this study, the characteristics of Ig-null B cells in high viral load carriers were examined by four-color flow cytometry. The frequency of Ig-null B cells in patients with high, low or undetectable virus loads was found that while patients with a high load had more Ig-null cells, these cells were also present in the low and undetectable load groups. As Ig-null cells from patients with no viral load were EBV-negative, EBV infection was not absolutely required for the generation or survival of Ig-null cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
0
10
1
Order By: Relevance
“…This patient was positive for EBER in situ expression at diagnosis, and if no rituximab was administered, then this may be the likely explanation. 23 Another interesting finding was that of a small bowel allograft recipient (BL-5), who had a negative for c-MYC rearrangement and absence of EBER in situ expression, despite the classic BL morphologic and immunohistochemical findings, including a proliferation rate >95% in the tissue. Others have shown that classic Burkitt morphological features with a very high proliferation fraction should still be considered as a BL, even when there is a negative MYC translocation.…”
Section: Discussionmentioning
confidence: 99%
“…This patient was positive for EBER in situ expression at diagnosis, and if no rituximab was administered, then this may be the likely explanation. 23 Another interesting finding was that of a small bowel allograft recipient (BL-5), who had a negative for c-MYC rearrangement and absence of EBER in situ expression, despite the classic BL morphologic and immunohistochemical findings, including a proliferation rate >95% in the tissue. Others have shown that classic Burkitt morphological features with a very high proliferation fraction should still be considered as a BL, even when there is a negative MYC translocation.…”
Section: Discussionmentioning
confidence: 99%
“…An analogous process is thought to account for virusmediated reprogramming of the B cell phenotype in classical Hodgkin lymphomas (176). Immunotherapy specifically targeting B cells, such as anti-CD20 antibody therapy, might be ineffective when the B cell phenotype is reprogrammed (170). Likewise, EBV may interfere with programmed cell death in B cells, potentially contributing to viral persistence, accumulation of somatic mutations, and neoplastic transformation (20, 21, 27, 169, 189).…”
Section: B Cell Lineage and Viral Reprogrammingmentioning
confidence: 99%
“…Interestingly, some cases of PTLD lack CD20 expression, and it is hypothesized that downregulation of CD20 and other B cell markers occurs in response to EBV infection (8,170). An analogous process is thought to account for virusmediated reprogramming of the B cell phenotype in classical Hodgkin lymphomas (176).…”
Section: B Cell Lineage and Viral Reprogrammingmentioning
confidence: 99%
“…The data showed that the median of maximum viral loads were significantly higher in the PTLD patients (4035 copies/mL) than nonaffected patients (500 copies/mL), consistent with several previous studies. [3][4][5] As we detected in this study, a wide range of EBV loads were observed in liver transplant patients. This was because of involvement of multiple host factors such as age of transplant, active primary infection, different underlying disease, immunosuppressive drug regimen, and intensity.…”
Section: Discussionmentioning
confidence: 48%
“…This ubiquitous virus 90% adults worldwide. [3][4][5] It is associated with different malignancies and disorders such as Hodgkin lymphoma, non-Hodgkin lymphoma, Burkitt lymphoma, nasopharyngeal carcinoma, gastric carcinoma, and posttransplant lympho proliferative disorders (PTLDs). 6,7 In immunocompetent individuals, EBV causes infectious mononucleosis, an acute but self-limited disease that affects children and young adults.…”
Section: Epstein-barr Virus (Ebv) Is a Member Ofmentioning
confidence: 99%